Impact of Professional Skepticism, Experience, Competence, and Time Pressure on Fraud Detection: Job Hierarchy Moderator - Nabila; Artie Arditha Rachman; Endang Asliana; Dewi Zakia; Surya Prasetya Trihatmaja (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM), STIE Krakatau, 2026)
This study was motivated by the significant financial losses resulting from financial statement fraud and the limited role of external auditors in detecting fraud in Indonesia. This study aims to analyze the impact of professional skepticism, experience, competence, and time pressure on the ability to detect financial statement fraud, with job hierarchy serving as a moderating variable. This study employs a quantitative approach using a survey method involving 266 auditors working at 83 public accounting firms in DKI Jakarta and Lampung regions. The research instrument consisted of a 4 point Likert scale questionnaire, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with Smart PLS 4. The novelty of this study lies in the integration of Weiner’s attribution theory and job hierarchy as a moderating variable, as well as the expansion of the focus to the local context of auditors in Lampung, which has not been extensively studied in the literature. The results show that professional skepticism, audit experience, competence, and time pressure influence the ability to detect financial-statement fraud. Job hierarchy moderates the effect of audit experience, whereas professional skepticism, competence, and time pressure do not. These findings imply that efforts to strengthen professional skepticism, audit experience, and competence, as well as manage time pressure, should be maintained, and the effectiveness of the job hierarchy in fraud detection should be evaluated.